Who Believes in Fake News? Identification of Political (A)Symmetries - João Pedro Baptista; Anabela Gradim (Social Sciences, 2022)
Political fake news continues to be a threat to contemporary societies, negatively affecting public and democratic institutions. The literature has identified political bias as one of the main predictors of belief and spread of fake news. However, the academic debate has not been consensual regarding the effect of political identity on the discernment of fake news. This systematic literature review (2017–2021) seeks to understand whether there is consistent evidence that one political identity may be more vulnerable to fake news than others. Focusing the analysis on European and North American (United States) studies, we used Scopus and Web of Science databases to examine the literature. Our findings revealed that most studies are consistent in identifying the conservative or right-wing audience as more vulnerable to fake news. Although there seems to be a motivated political reasoning for both sides, left-wing people or liberals were not, in any analyzed study, associated with a greater propensity to believe in political fake news. Motivated reasoning seems stronger and more active among conservatives, both in the United States and Europe. Our study reinforces the need to intensify the fight against the proliferation of fake news among the most conservative, populist, and radical right audience.